Daurinol Enhances the Efficacy of Radiotherapy in Lung Cancer via Suppression of Aurora Kinase A/B Expression - Woo, Jong Kyu; Kang, Ju-Hee; Shin, DongYun; Park, Seong-Hyeok; Kang, Kyungsu; Nho, Chu Won; Seong, Je Kyung; Lee, Sang-Jin; Oh, Seung Hyun (AMER ASSOC CANCER RESEARCH, 2015)
The aurora kinases constitute one family of serine/threonine kinases whose activity is essential for mitotic progression. The aurora kinases are frequently upregulated in human cancers and are associated with sensitivity to chemotherapy in certain ones. In the present study, we investigated whether aurora kinases could be a target to overcome radioresistance or enhance the radiosensitivity of lung cancer. For that purpose, we determined the therapeutic potential of daurinol, an investigational topoisomerase inhibitor, alone and in combination with radiation, by observing its effect on aurora kinases. Daurinol decreased cell viability and proliferation in human colon and lung cancer cells. Gene expression in daurinol-treated human colon cancer cells was evaluated using RNA microarray. The mRNA expression of 18 genes involved in the mitotic spindle check point, including aurora kinase A (AURKA) and aurora kinase B (AURKB), was decreased in daurinol-treated human colon cancer cells as compared with vehicle-treated cells. As expected, radiation increased expression levels of AURKA and AURKB. This increase was effectively attenuated by siRNAs against AURKA and AURKB, which suppressed cell growth and increased apoptosis under radiation. Furthermore, the expression of AURKA and AURKB was suppressed by daurinol in the presence or absence of radiation in colon and lung cancer cells. Daurinol alone or in combination with radiation decreased lung cancer growth in xenograft mouse models. Our data clearly confirm the antitumor and radiosensitizing activity of daurinol in human lung cancer cells through the inhibition of AURKA and AURKB. (C) 2015 AACR.
Keywords: SMALL-MOLECULE INHIBITOR; CONCURRENT CHEMORADIATION; FRACTIONATED-IRRADIATION; RADIATION RESPONSE; CELL-DEATH; PHASE-III; A KINASE; COMBINATION; DOCETAXEL; APOPTOSIS